ELECTRIC PULP TEST OF TEETH WITH PERIODONTAL DISEASE. - Tsonko Uzunov; Raya Grozdanova; Dimitar Kosturkov; Albena Latkovska; Todor Ts. Uzunov (Peytchinski Publishing, 2014)
Purpose: The aim of the research is to investigate the change in pulp vitality of teeth with periodontal disease using electric pulp tester (EPT). Methods: Subjected to observation were 108 patients with chronic periodontitis. Vitality of 805 teeth with periodontal pocket depth greater than 4 mm was studied by EPT. The research was conducted with EPT "Yonovit ". Results: The highest percentage of surveyed teeth (68.4%) respond to the norm when they are tested with EPT - values between 3 μA and 10 μA . Teeth that respond to EPT with values ​​below 3 μA and between 35-100 μA are relatively equal - respectively 4.3% and 3.3%. With increased threshold of irritation - 10-35 μA react 23.4% of teeth. Small number of teeth have threshold of irritation over 100 μA - 0.6%. Conclusion: The value of EPT among periodontal damaged teeth depends on many factors - patient's age, extent of periodontal affect, group affiliation of teeth, etc.